Adapting the Balanced Scorecard to an economic: the case of the wine sector of the Alentejo Region - context, bibliographic review and methodological proposal - Gomes, Maria José (2017)
This article, based on an ongoing research project, presents a methodological research proposal on the Balanced Scorecard Methodology applied to an economic sector (wine sector) in a Portuguese region (Alentejo) and presents a synthesis of the state of art of the Methodology. The "convergent parallel design" method was used and the data will be collected through qualitative research (interviews) and quantitative (questionnaires) and documents about the Wine Sector. The contribution focuses on the attempt to mitigate the gap problem due to the inexistence of a strategic management referential for the Wine Sector of the Alentejo Region for the period 2018-2022, by constructing four pieces: Value Proposition for Clients, Vision, Strategy and Scorecard Map. It can be concluded that the Balanced Scorecard Methodology can be applied to an entire economic sector.